Impact of implementing hourly rounding on improving patient satisfaction: A literature review - Lency Karnovty Maria; Blacius Dedi (Program Studi Ilmu Keperawatan-fakultas Ilmu Kesehatan Universitas Malahayati, 2024)
Background: Nursing rounds are an implementation of Relationship Based Care. Implementation of nursing rounds allows nurses to have reciprocal relationships with patients and families on a regular and systematic basis. Periodic rounds have been used throughout the world in nursing care to anticipate patient needs while utilizing evidence-based interventions. Purpose: To determine the effectiveness and impact of implementing hourly rounding on improving patient satisfaction Method: A literature review design. The databases used include Google Scholar, Pubmed, and Semantic Scholar. English keywords employed are